Pengaruh Servant Leadership dan Lingkungan Kerja Melalui Kepuasan Kerja terhadap Kinerja Pegawai pada Bank Pembangunan Daerah Jambi Kantor Cabang Bangko - Denny Karyadi; Pantun Pantun; Mufidah Mufidah (J-MAS (Jurnal Manajemen dan Sains), 2026)
This study aims to analyze the effect of servant leadership and work environment on employee performance at Bank Pembangunan Daerah (BPD) Jambi, Bangko Branch Office, both directly and indirectly through job satisfaction. The dynamics of the regional banking industry demand high operational performance stability amidst fluctuating credit targets and third-party funds. The research method used is quantitative descriptive with a census approach (total sampling) involving all 64 operational employees. Data was collected via structured questionnaires with a 5-point Likert scale and analyzed using Path Analysis technique powered by IBM SPSS Statistics. The descriptive results indicate that servant leadership, work environment, job satisfaction, and employee performance are all perceived in a good category. The t-test (partial) results indicate that servant leadership has a positive but non-significant direct effect on employee performance (β = 0.159; p > 0.05), whereas the work environment has a positive and significant direct effect on employee performance (β = 0.611; p < 0.05). Furthermore, the simultaneous test (F-test) for the total effect model (Sub-Structure 2) shows an F-statistic value of 28.487 with a significance level (p < 0.05), confirming that all independent variables jointly contribute significantly to the model. The path model demonstrates that job satisfaction serves as a significant intervening variable that bridges the influence of both servant leadership and work environment towards the total enhancement of employee performance (with an R-Square contribution of 63%). Managerial implications highlight the necessity of cultivating a supportive leadership climate and maintaining physical workspace facilities to drive internal job satisfaction.